An Antennae-Specific Odorant-Binding Protein Is Involved in Bactrocera dorsalis Olfaction - Liu, Zhao; Liang, Xiao-Fei; Xu, Li; Keesey, Ian W.; Lei, Zhong-Ren; Smagghe, Guy; Wang, Jin-Jun (Frontiers in Ecology and Evolution, 2020)
Insect antennae are important olfactory organs that house high concentrations of odorant-binding proteins (OBPs) in the sensillum lymph. Previous studies in other insects have shown that OBPs play important roles in transporting odorants and enhancing the sensitivity of the olfactory system. However, the functions of OBPs in the oriental fruit fly, Bactrocera dorsalis, especially the functions of the antennae-specific OBPs, have not been fully elucidated. In this study, cDNA libraries were constructed from both the male and female antennal transcriptome, and twenty OBPs were identified in total. The expression profiles of these OBPs were examined in the adult antenna, head, thorax, leg, and abdomen of both sexes. Seven of the identified OBP genes had significantly higher expression in both the male and female antennae than in other tissues, while the transcript levels of the remaining OBPs varied across the different tissues. In order to examine the function of antenna-specific OBPs, we targeted Bdorsobp2 for RNA interference (RNAi) and identified via electrophysiology a decrease in detection of this insect’s novel attractant, methyl eugenol. Moreover, our data showed that the behavioral response of B. dorsalis towards this odorant decreased when Bdorobp2 was silenced with injection of double-stranded RNA (dsRNA). Combined, these results support our initial hypothesis that antennae-specific OBPs are of critical importance for insect odorant detection and sensitivity.